2018
DOI: 10.1097/01.aoa.0000529999.63529.53
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations With Gestational Duration and Spontaneous Preterm Birth

Abstract: BACKGROUNDDespite evidence that genetic factors contribute to the duration of gestation and the risk of preterm birth, robust associations with genetic variants have not been identified. We used large data sets that included the gestational duration to determine possible genetic associations. METHODSWe performed a genomewide association study in a discovery set of samples obtained from 43,568 women of European ancestry using gestational duration as a continuous trait and term or preterm (<37 weeks) birth as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(177 citation statements)
references
References 18 publications
9
166
1
1
Order By: Relevance
“…Single nucleotide polymorphisms of TGFBR3 have been found to be associated with gestational duration. 53 Various cytokines have also been associated with spontaneous preterm birth. 54 However, cytokines were below the detection threshold in our mass spectrometry analysis precluding comparisons.…”
Section: Commentmentioning
confidence: 99%
“…Single nucleotide polymorphisms of TGFBR3 have been found to be associated with gestational duration. 53 Various cytokines have also been associated with spontaneous preterm birth. 54 However, cytokines were below the detection threshold in our mass spectrometry analysis precluding comparisons.…”
Section: Commentmentioning
confidence: 99%
“…The similar signaling pathways associated with WNT4 in ILC and OvCa may parallel the critical role of WNT4 in the tissues of origin, as well as related tumor biology. In addition to being required for mammary gland development, WNT4 is required for the development of the ovary and Mullerian tissues [45,56], female sex differentiation [56,57], and fertility [46,58]. Accordingly, WNT4 dysfunction is linked to a range of endocrine and gynecologic pathologies, including endometriosis [59], uterine fibroids [60], and ovarian cancer [61].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous data demonstrated that genetic factors contributed to gestational length and risk of preterm birth (12), non-genetic factors may also influence oxidative stress and redox system imbalances in the maternal-foetal intrauterine compartment (13). Maternal lifestyle (14) and health status, including diseases with onset prior to or during pregnancy (15), may influence oxidative stress and affect the apoptotic pathway leading to at-term birth or sPTB, both of which also appear consequent to a mechanism involving genetic and non-genetic factors, which may modulate the oxidative stress-induced apoptosis.…”
Section: Induction Of the Apoptotic Pathway By Oxidative Stress Inmentioning
confidence: 94%